Consumption Behaviour Towards Green Durable Products : The Moderating Role of Demographics - Ghose, Amitabha; Chandra, Bibhas (Indian Journal of Marketing, 2018)
India is the fourth largest consumer durable product market in the world. However, due to its rapidly changing economic environment, divide between urban and rural markets and heterogeneous demographic regions, it presents unique marketing challenges for green consumer durable products. In order to attain a better understanding of Indian consumers’ behaviour as a potentially highly valuable green consumer durable product market, we developed 11 hypotheses with relevant literature support and represented them in a conceptual framework. The framework was tested with primary data by obtaining structural equation modeling results to measure the correlation among the constructs, and chi-square results and goodness of fit indices were also analyzed. We conducted a survey of 472 Indian nationals across India to collect primary data. Data analysis found a very good fit of our model and obtained support for almost all the hypotheses. We also tested a proposed conceptual framework with demographics (location of living, income, qualification, and gender) as moderating variables. The results from regression analysis indicated that location of living was a significant moderating factor, while income, qualification, and gender did not register as significant.